2015
DOI: 10.5958/0976-0547.2015.00010.5
|View full text |Cite
|
Sign up to set email alerts
|

Mass media utilization behaviour of farm women

Abstract: Farm women are the backbone of Indian agriculture. They represent the invisible work forces in a gamut of activities ranging from land preparation till harvest of the agricultural produce. The mass media utilization behavior of farm women is central to equipping women with the latest developments in farming technology and honing their technical skills which leads to their increased productivity in their farm and home. A study was conducted on a sample of 30 farm women to analyze their mass media utilization be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similar results were also found by Srinivas and Venkatrayalu (2016). Lekshmi et al, (2005) reported that 40 percent had collegiate level of education in shrimp farmers and 30 percent of shrimp farmers had primary education in Andhra Pradesh. Ogunmefun and Achike (2017) also reported that the majority (60%) of the respondents possessing secondary education and 37% were found to possess tertiary education with only very few (3%) respondents indicating to have only completed primary education.…”
Section: Basic Details Of Farmersmentioning
confidence: 99%
“…Similar results were also found by Srinivas and Venkatrayalu (2016). Lekshmi et al, (2005) reported that 40 percent had collegiate level of education in shrimp farmers and 30 percent of shrimp farmers had primary education in Andhra Pradesh. Ogunmefun and Achike (2017) also reported that the majority (60%) of the respondents possessing secondary education and 37% were found to possess tertiary education with only very few (3%) respondents indicating to have only completed primary education.…”
Section: Basic Details Of Farmersmentioning
confidence: 99%